Intellectual capital: mediator of board of directors’ effectiveness and adoption of International Financial Reporting Standards - Tumwebaze, Zainabu; Bananuka, Juma; Alinda, Kassim; Kalembe, Dorcus (Journal of Financial Reporting and Accounting, 2020)
The purpose of this paper is twofold: to test whether intellectual capital mediates the relationship between board of directors’ effectiveness and adoption of International Financial Reporting Standards (IFRS) and to examine the contribution of the specific elements of intellectual capital and board of directors’ effectiveness to adoption of IFRS. Design/methodology/approach – This study is cross-sectional. Usable questionnaires were received from 67 microfinance institutions (MFIs) that are members of the Association of MFIs of Uganda. The data was analyzed using Statistical Package for Social Sciences and MedGraph program (Excel version). Findings – Results indicate that intellectual capital mediates the relationship between board of directors’ effectiveness and adoption of IFRS. Results further indicate that board independence and board meetings contribute significantly to the adoption of IFRS unlike board size and board committees. Results also indicate that in the intellectual capital elements, only structural capital and human capital significantly contribute to the adoption of IFRS unlike relational capital. Originality/value – This study provides more insights on our understanding of the relationship between intellectual capital, board of directors’ effectiveness and adoption of IFRS. Specifically, it provides first time evidence of the mediation effect of intellectual capital in the relationship between board of directors’ effectiveness and adoption of IFRS using evidence from an African developing country – Uganda. Further, this paper adds to existing literature on corporate governance and reporting practices, as it provides more
Keywords: Uganda; Intellectual capital; Adoption of IFRS; Microfinance institutions; Board of directors’ effectiveness